Private capital incentive model in public-private partnership projects for the development of public infrastructure - Ivanov Viktor; Zhou Jiashu; Andrianov Alexander (E3S Web of Conferences, 2023)
Public infrastructure development is considered to be the basis for comfortable living conditions of all the citizens. Therefore, the optimization of public infrastructure should be treated as an important task of any government. The Public-Private Partnership (hereinafter referred to as PPP) model makes it possible to reduce financial pressure on the government budget, to accelerate the construction of public infrastructure and to enhance the efficiency of investment management. The analysis of Russian experience [1], as well as the experience of a number of foreign countries [2], indicates that many issues of financial support, including the issues of reimbursement of costs to public-private partnership entities, have not been sufficiently developed in terms of law and economics. The interval model of a linear compensation mechanism as applied to Chinese PPP models is proposed in this paper. The authors analyze three types of models for subsidizing PPPs by the Chinese government: rate of return model for discounted construction costs; model of discounted construction costs; rate of return model for discounted average construction costs at the beginning of the period. The mechanism for establishing a range of state compensation for additional costs of a private investor due to a reduction in construction time is proposed in the article.